OVERVIEW OF POWER FLOW ENHANCEMENT BY USING THYRISTOR CONTROLLED SERIES CAPACITOR (TCSC) - MR. VISHAL RAJENDRA MEHTA; PROF. L. S. PATIL (International Journal of Innovations in Engineering Research and Technology, 2021)
Power quality has become one of the most important concerns now a day as the nature of loads changing with new technologies and developments. Non-linear nature of loads leads to the deterioration of power quality. Power system losses and the reliability of power are the important apprehensions to address the issues of power quality. With increasing number of small power generating stations using renewable energy, the problems associated with quality of power are increasing. The enhancement of the quality of power with different combinations of the controlling strategies is proposed by the researchers over last decade and many such solutions are implemented in the power system. Authors have presented the overview of solutions suggested by researchers to enhance the quality of power in the paper.